Cryogenic mouse tissue homogenization as an alternative to fresh-frozen biopsy use for genomics, transcriptomics, proteomics and metabolomics - Laimdota Zizmare; Ute Hofmann; Mohamed Ali Jarboui; Franziska Klose; Sabine Fraschka; Jakob Matthes; Marcel Krüger; Elke Schaeffeler; Matthias Schwab; Marius Ueffing; Bernd J. Pichler; Karsten Boldt; et al. (Scientific Reports)
Abstract The classical approach of using adjacent pieces of fresh-frozen tissue for various omics analysis from the same sample possesses a risk of biological mismatch between arising from intrinsic tissue heterogeneity. We propose an alternative approach of tissue cryogenic pulverization and lyophilization before distribution for omics studies for a more reliable analysis. Here, we compare individual omics layer readouts from fresh-frozen adjacent tissue pieces and homogenized powder in mouse brain, kidney, and liver. Genomics, transcriptomics, proteomics, and metabolomics analyses showed comparable RNA integrity, DNA methylation, and coverage of transcripts, proteins, and metabolites across both methods. Moreover, the homogenized-lyophilized powder usage led to reduced heterogeneity between biological replicates. We conclude that the cryogenically pulverized-lyophilized tissue approach not only maintains a critical molecular feature coverage and quality but also provides a homogenous basis for various omics analysis enhancing reproducibility, sample transport, storage and enabling multi omics base on one and the same tissue aliquot.